Power Apps pada Sistem Pemodelan Pengambilan Obat di Klinik Melia PT. POMI, Paiton - Primasanti, Yunita (Prodi Teknik Industri, Universitas AKPRIND Indonesia, 2022)
Digitalization is one of the important keys in increasing productivity, namely by building digital technology that improves process efficiency, product and service quality, and optimizes resource allocation, so as to reduce processing time for faster, streamlined operations, and greater customer satisfaction. as good as Power Apps. Power Apps is a service for building and deploying custom business applications that connect to your data and work across the web and mobile - without the time and expense of specialized software development. Power Apps are a number of applications, services, and connectors, as well as a data platform, that provide a fast development environment for building custom applications for business needs. Using Power Apps, users can quickly create custom business applications that connect to data stored on the base data platform (Microsoft Dataverse) or across various online and on-premises data sources (such as SharePoint, Microsoft 365, Dynamics 365, SQL Server, and so on). The purpose of this study is to implement and analyze the use of Power Apps in modeling drug retrieval at the Melia Clinic PT POMI, Paiton with the aim of improving the quality of Melia clinic services through acceleration and ease of drug taking. The output of this research is an accredited national journal.